Cp2TiCl/D2O/Mn, a formidable reagent for the deuteration of organic compounds - Rosales, Antonio; Rodríguez-García, Ignacio (Beilstein Journal of Organic Chemistry, 2016)
Cp2TiCl/D2O/Mn is an efficient combination, sustainable and cheap reagent that mediates the D-atom transfer from D2O to different functional groups and can contribute to the synthesis of new deuterated organic compounds under friendly experimental conditions and with great economic advantages.
Keywords: deuteration; deuterium atom transfer; radical and/or organometallic chemistry; titanocene